The Impact of Cash Budgets on Poverty Reduction in Zambia : A Case Study of the Conflict between Well-Intentioned Macroeconomic Policy and Service Delivery to the Poor - Dinh, Hinh (The World Bank, 2002)
Facing runaway inflation and budget discipline problems in the early 1990s, the Zambian government introduced the so-called cash budget in which government domestic spending is limited to domestic revenue, leaving no room for excess spending. Dinh, Adugna, and Myers review Zambia's experience during the past decade, focusing on the impact of the cash budget on poverty reduction. They conclude that after some initial success in reducing hyperinflation, the cash budget has largely failed to keep inflation at low levels, created a false sense of fiscal security, and distracted policymakers from addressing the fundamental issue of fiscal discipline. More important, it has had a deeply pernicious effect on the quality of service delivery to the poor. Features inherent to the cash budgeting system facilitated a substantial redirection of resources away from the intended targets, such as agencies and ministries that provide social and economic services. The cash budget also eliminated the predictability of cash releases, making effective planning by line ministries difficult. Going forward, Zambia must adopt measures that over time will restore the commitment to budget discipline and shelter budget execution decisions from the pressures of purely short-term exigencies. This paper—a product of the Poverty Reduction and Economic Management Division 1, Africa Region—is part of a larger effort in the region to review public expenditure management